Towards elimination of lymphatic filariasis in southeastern Madagascar: Successes and challenges for interrupting transmission. - Andres Garchitorena; Estelle M Raza-Fanomezanjanahary; Sedera A Mioramalala; Cédric B Chesnais; Claude A Ratsimbasoa; Herinirina Ramarosata; Matthew H Bonds; Holivololona Rabenantoandro (Public Library of Science (PLoS), 2018)
INTRODUCTION:A global strategy of mass drug administration (MDA) has greatly reduced the burden of lymphatic filariasis (LF) in endemic countries. In Madagascar, the National Programme to eliminate LF has scaled-up annual MDA of albendazole and diethylcarbamazine across the country in the last decade, but its impact on LF transmission has never been reported. The objective of this study was to evaluate progress towards LF elimination in southeastern Madagascar. METHODS:Three different surveys were carried out in parallel in four health districts of the Vatovavy Fitovinany region in 2016: i) a school-based transmission assessment survey (TAS) in the districts of Manakara Atsimo, Mananjary, and Vohipeno (following a successful pre-TAS in 2013); ii) a district-representative community prevalence survey in Ifanadiana district; and iii) a community prevalence survey in sentinel and spot-check sites of these four districts. LF infection was assessed using the Alere Filariasis Test Strips, which detect circulating filarial antigens (CFA) of adult worms. A brief knowledge, attitudes and practices questionnaire was included in the community surveys. PRINCIPAL FINDINGS:None of the 1,825 children sampled in the TAS, and only one in 1,306 children from sentinel and spot-check sites, tested positive to CFA. However, CFA prevalence rate in individuals older than 15 years was still high in two of these three districts, at 3.5 and 9.7% in Mananjary and Vohipeno, respectively. Overall CFA prevalence in sentinel and spot-check sites of these three districts was 2.80% (N = 2,707), but only two individuals had detectable levels of microfilaraemia (0.06%). Prevalence rate estimates for Ifanadiana were substantially higher in the district-representative survey (15.8%; N = 545) than in sentinel and spot-check sites (0.8%; N = 618). Only 51.2% of individuals surveyed in these four districts reported taking MDA in the last year, and 42.2% reported knowing about LF. CONCLUSIONS:Although TAS results suggest that MDA can be stopped in three districts of southeastern Madagascar, the adult population still presents high CFA prevalence levels. This discordance raises important questions about the TAS procedures and the interpretation of their results.